Case report: successful open resection of a symptomatic giant liver haemangioma during the second trimester of pregnancy. (3rd November 2016) - Hann, Angus; Osenda, Edoardo; Reade, Jon A.; Economides, Demetrius; Sharma, Dinesh
Abstract: Liver haemangiomas are consistently reported to be the commonest benign liver tumours and are most often incidental findings in asymptomatic individuals. Large lesions can become symptomatic, spontaneously rupture or result in a consumptive coagulopathy known as Kasabach–Merrit Syndrome. It is believed that the female sex hormones, particularly oestrogen, have an influence on haemangioma development and growth. The optimal management of large haemangiomas during the hyperoestrogenic state of pregnancy is poorly described in the current literature. To our knowledge, we describe only the second case of a giant hepatic haemangioma resection during pregnancy.